2014
DOI: 10.1088/2040-8978/16/11/114019
|View full text |Cite
|
Sign up to set email alerts
|

Loss and scattering of surface plasmon polaritons on optically-pumped hole arrays

Abstract: We study surface plasmons on two-dimensional square arrays of sub-wavelength holes in a gold film deposited on an optically-excited semiconductor. We observe four resonances of which we measure the resonance frequencies, the spectral widths, and the relative intensities. The spectral widths allow us to quantify various loss processes, including ohmic loss, optical absorption/gain and radiative scattering loss. Prominent kinks in the plasmon dispersion relation occur around the Rayleigh anomaly. A coupled mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 20 publications
3
39
0
Order By: Relevance
“…Letter and refractive index n 0 = 3.268, 24 corresponding to κL = 8. The calculated near field shown in Figure 3a contains the essential features of Figure 3c: it has two lobes with opposite sign, indicated by a π-phase jump in the center of the device.…”
Section: Acs Photonicsmentioning
confidence: 99%
“…Letter and refractive index n 0 = 3.268, 24 corresponding to κL = 8. The calculated near field shown in Figure 3a contains the essential features of Figure 3c: it has two lobes with opposite sign, indicated by a π-phase jump in the center of the device.…”
Section: Acs Photonicsmentioning
confidence: 99%
“…The layer-stack is designed such that it only supports the TM-like SP-mode. Square hole arrays with a similar layer-stack are described in more detail in refs [9,11,12].…”
Section: Methodsmentioning
confidence: 99%
“…The SP are excited by spontaneous emission from the optically pumped InGaAs gain layer. The same setup was used in refs [9,11,12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve a low threshold, narrow spectrum, and a controlled radiation pattern, periodic plasmonic structures are preferable. For these reasons, plasmonic distributed feedback (DFB) lasers are being actively investigated . It has been recently demonstrated that the response frequency of a plasmonic DFB laser in a large‐signal modulation scheme can exceed several hundred gigahertz …”
mentioning
confidence: 99%